Soil microbial community dynamics associated with agricultural crops - Lichtner, Franz Johann, author; Broders, Kirk Dale, advisor; Schipanski, Meagan, committee member; Smith, Richard G., committee member; Wallenstein, Matthew D., committee member (Colorado State University. Libraries, 2018)
It could be argued that the sustainability of agriculture hinges on our ability to understand and manage the interactions that occur between agricultural crops and microbial communities that reside in the soil. Soil microbes regulate the decomposition of organic matter, the cycling of nutrients to crops and can induce systemic resistance. They also drive global biogeochemical cycles that influence the climate, which in turn determine the growing environment for crops. Soil microbes also interact with crop plants directly via neutral, pathogenic, or beneficial symbioses that can influence plant health as well as resistance and resilience to pests and abiotic stress. Conversely, crop plants, via their growth, root exudation and litter production, are critical to the maintenance and growth of soil microbe populations. Despite their close association and importance to global agriculture, our understanding of the interactions between crop plants and their associated soil microbial communities remains poorly understood. In this dissertation I conducted experiments in two agro-ecoregions (the US Northeast and the Southern mountains of Colorado) to better understand how crop plant composition and management influence soil microbial communities and populations of pathogenic microbes. Data from the first experiment are reported in Chapters 1 and 2. In this experiment I sampled soil microbial communities in a field experiment that was replicated across four locations in the Northeast US. The experimental treatments were plots of perennial ryegrass varying in perennial ryegrass genotypic composition and diversity. My objective was to determine whether the genotypic composition and diversity of the perennial ryegrass stand influenced the structure (Chapter 1) and composition (Chapter 2) of the soil microbial community over the years of the experiment. I found that soil microbial community structure (measured as abundance of bacteria and fungi) and composition was not influenced by the cultivar mixtures, but rather by the year, location, and plant biomass. In chapter 3 I present data from a survey of Helminthosporium solani and Colletotrichum coccodes and a controlled experiment on their effects on potato cultivars in post-harvest storage. The objective of these studies was to understand how specific fungal-fungal and fungal-plant interactions are important in a potato production system where the functional aspects of a specific microbial community is not well understood. Here we see an annual change in soil pathogen presence depending on crop plant in the field. My results show that microbial interactions are polymodal and dependent on host genotype, soil chemical and physical properties and management practices. My final objective in this dissertation was to formally describe a fungal species, Penicillium acequia sp. nov. This fungal species was prevalent in agricultural soils and morphologically and genetically different from its closest relative. This new species has potential to be cultured and utilized as a biocontrol or for production of valuable secondary metabolites. Fungal antagonism as an option for crop plant disease control could reduce overall fungicide use. Inoculation of perennial cropping systems with beneficial microbes at planting over multiple years could harbor a soil microbiome that requires fewer inputs with reduced disease. We have a long way to go in describing the diversity of life in the soil that is critical to our food production system, and must characterize the presence and function of microbes within agricultural systems. Collectively, the data from this dissertation suggests that there are important yet opaque outcomes of microbial interactions influenced by time and location among other variables. Host genetics, including resistance genes, allow for unique microbial interactions and nutrient exchange which may matter more than traditional phenotypic plant traits, though this requires more research. Microbial interactions continue to evolve, the importance of genetic quantity is not to be discounted, rather determining the biologic pathways mediating interactions will provide greater insight into the sustainability of agricultural ecosystems.
Keywords: fungi; penicillium; potato; microbiome; agroecosystem; perennial crop